Respuesta :

The Question is Incomplete Assume to find u ? in this Question may help you

Answer:

Therefore.

[tex]u = -21.74[/tex]

Step-by-step explanation:

Given:

Expression is

[tex]-10.74=u-(-11)[/tex]

To Find:

u = ? Assumption

Solution:

Here use PEMDAS rule

PEMDAS is an acronym for the words

P ----------> Parenthesis,

E ----------> Exponents,

M ---------> Multiplication,

D ----------> Division,

A -----------> Addition,

S -----------> Subtraction.

For any expression, all Parenthesis should be simplified first, followed by Exponenents, multiplication and division from left to right and, finally, addition and subtraction from left to right.

Step 1: Given

[tex]-10.74=u-(-11)[/tex]

Step 2 : First operate Parenthesis where minus , minus will become plus

[tex]-10.74=u+11[/tex]

Step 3: Subtract 11 to both the sides

[tex]-10.74-11=u+11-11\\-21.74=u[/tex]

Step 3: Final solution

[tex]u = -21.74[/tex]

Therefore.

[tex]u = -21.74[/tex]

ACCESS MORE